2018
DOI: 10.3390/jcm7100337
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Brain—Is Resistance Training with Blood Flow Restriction an Effective Strategy for Cognitive Improvement?

Abstract: Aging is accompanied by a decrease in physical capabilities (e.g., strength loss) and cognitive decline. The observed bidirectional relationship between physical activity and brain health suggests that physical activities could be beneficial to maintain and improve brain functioning (e.g., cognitive performance). However, the exercise type (e.g., resistance training, endurance training) and their exercise variables (e.g., load, duration, frequency) for an effective physical activity that optimally enhance cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 280 publications
(409 reference statements)
2
19
0
Order By: Relevance
“…As shown in Fig. 1, cognitive improvements in response to resistance exercises and/or resistance training are based on changes on multiple levels of analysis [112,113]. At the first level, molecular and cellular changes occur, which are summarized in the "neurotrophic hypothesis" [114][115][116][117].…”
Section: Resistance Exercises Resistance Training Brain and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 1, cognitive improvements in response to resistance exercises and/or resistance training are based on changes on multiple levels of analysis [112,113]. At the first level, molecular and cellular changes occur, which are summarized in the "neurotrophic hypothesis" [114][115][116][117].…”
Section: Resistance Exercises Resistance Training Brain and Cognitionmentioning
confidence: 99%
“…Furthermore, it was reported that improvements in executive functions were larger after moderate-load (70% of 10RM) than low-load (40% of 10RM) resistance exercises [156]. The finding that resistance exercises with moderate loads are especially beneficial for cognitive performance is supported by the observation that resistance exercises with moderate loads (60% 1RM) lead to larger positive effects on higher cognitive functions (i.e., Stroop interference score) Table 3 Overview of exercise variables and training variables [60,113,[354][355][356] Variables for structuring a single resistance exercise session (exercise variables) compared with resistance exercises with heavier loads (≥ 75% 1RM) [360]. In another study, it was noticed that a single bout of high-load (100% of 10RM) resistance exercises resulted in less interference and fastened reaction times for the Stroop task 15 min after exercise cessation, while 180 min after exercise cessation, low-load (40% of 10RM) and moderate-load (70% of 10RM) resistance exercises were associated with increased performance on the plus-minus and the Simon task [146].…”
Section: Influence Of Exercise Variables and Training Variables On Nementioning
confidence: 99%
“…There is growing evidence in the literature that acute resistance exercises and long-term resistance training improve cognitive functions [1][2][3][4]. However, the underlying mechanisms for these cognitive improvements are not fully understood yet, although they seem to rely on changes at multiple levels [5][6][7]. One assumption is that resistance exercises may act as an 'indirect' form of cognitive training since for their execution subjects need to constantly engage cognitive resources as they have to pay attention to perform the movement with an appropriate technique (e.g., squat), to produce an appropriate level of force, and to observe the surroundings in order not to harm themselves or others [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the product of exercise intensity, exercise duration, and type of physical exercise is commonly referred to as the dose [33,136], whereas a newer approach refines this definition and proposes that this dose can be objectified by using a specific marker(s) of the internal load as a proxy [29,138]. However, the dose-response relationship between acute physical exercise, cognition, and the underlying neurobiological processes (e.g., changes in cerebral hemodynamics) is currently poorly understood [26,33,35,146]. While one study provides clear evidence that brain activation patterns and cognitive performance are influenced by the exercise protocol [101], the remaining reviewed studies are too heterogeneous with regard to their studied exercise variables (e.g., exercise intensity and exercise duration) and too homogeneous with regard to the type of physical exercise they examine (only endurance exercises, such as stationary cycling or treadmill running) to derive solid conclusions in this direction.…”
Section: Exercise Characteristicsmentioning
confidence: 99%
“…However, the underlying neurobiological mechanisms of these effects are not yet fully understood. In this regard, the use of neuroimaging methods offers great potential for acquiring a deeper understanding of physical exercise-induced changes in the neural correlates of cognition, such as changes in functional brain activation [33][34][35]. The most common methods used to investigate effects on functional brain activation are functional near-infrared spectroscopy (fNIRS) [34] and electroencephalography (EEG) [36,37]; however, also functional magnetic resonance imaging (fMRI) has recently been applied in the context of acute physical exercise and cognition [38,39].…”
mentioning
confidence: 99%